Operative design : a catalogue of spatial verbs - Di Mari, Anthony; Yoo, Nora. (Amsterdam, The Netherlands : BIS Publishers, 2012)
The core idea for this project is to use operative verbs as tools for designing space. These operative verbs abstract the idea of spatial formation to its most basic terms, allowing for an objective approach to create the foundation for subjective spatial design.
Introduction -- Operations -- Combinations -- Aggregations -- Implementations.
Includes bibliographical references.
Keywords: Drawing -- Technique; Space (Art); Space (Architecture)